Toxicological Evaluation of Aqueous Leaf Extract of Chromolaena Odorata in Male Wistar Albino Rats - Asomugha RN, Okafor PN, Ijeh II, Orisakwe OE, Asomugha AL, Ndefo JC (Journal of Applied Pharmaceutical Science, 2013)
To evaluate the toxicological implications of the administration of aqueous leaf extract of Chromolaena odorata. The aqueous leaf extract was administered three times per week, for 90 days at doses of 161.5mg/kg, 32 3mg/kg, 538,5mg/kg and 1077mg/kg body weight, respectively. The control animals received 0.5ml of deionised water alone. The animals were sacrificed at the end of 90days. Blood samples were collected for biochemical analysis, and the heart, testes and kidney harvested for histological analysis. Histopathological examination of the heart, lungs, testis and the kidneys did not show any observable morphological alterations. The biochemical parameters; amylase, albumin and total serum protein, and Na+ were found to be decreased at doses of 538.5mg/kg and 1077mg/kg, while the serum levels of creatine kinase, AST, K+, glucose, uric acid, urea and creatinine were increased at the same dose levels. The absence of exhibition of observable toxicity below 538.5mg/kg body weight suggests that the extract may be safe and non-toxic only at very low doses.
Keywords: Chromolaena Odorata, Histopathology, Toxicity Study, leaf extract.